Pendidikan Kedisiplinan Anak Berbasis Keluarga di Desa Mekar Jaya - Tedy Prasetyo; Syahrul (Yayasan Ishlahul Muslimin Konawe Selatan, 2025)
The purpose of this research is to describe the form of family-based child discipline education and the problems faced by parents in providing family-based child discipline education in Mekar Jaya Village, North Moramo District, South Konawe Regency. This research is a type of qualitative research with descriptive analysis. This research was conducted in Mekar Jaya Village, North Moramo District, South Konawe Regency. The type of data that the author uses is qualitative data obtained from internal data and external data. In this study the authors used data sources, namely primary data sources and secondary data sources. Data collection techniques are carried out by means of observation, interviews, and documentation, namely data collection activities through various written data sources, both related to objective conditions and other supporting data. The analysis technique uses data reduction, data display and conclusion drawing/verification. Based on the analysis of the research results, it was concluded that the forms of family-based child discipline education in Mekar Jaya Village were (1) Time discipline by getting up early, limiting playing time (watching TV, playing cellphones and online games), (2) Discipline in dressing, (3 ) Discipline behave politely. In providing the basics of education to children, parents in the village of Mekar Jaya apply elements of discipline: there are family rules, there are punishments, there are rewards, and there is consistency. The problems faced by parents in providing family-based discipline education for children in Mekar Jaya village are (1) problems in time discipline, (2) problems in clothing discipline, (3) problems in discipline in polite behavior, (4) busy parents, (5) external or environmental influences